1991
DOI: 10.1577/1548-8675(1991)011<0572:pcaaho>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Population Characteristics and Angler Harvest of White Crappies in Four Large Missouri Reservoirs

Abstract: Populations of white crappie Pomoxis annularis were studied at four Missouri reservoirs to determine population characteristics and develop techniques to improve the quality of fishing. Trap‐netting in October was used to sample white crappies in Stockton, Pomme de Terre, Lake of the Ozarks, and Wappapello reservoirs. At all four reservoirs, trap‐net capture rates for year‐classes that were age‐2 or older were significantly correlated with estimated harvests the following year. Growth rates were consistently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 10 publications
2
63
2
Order By: Relevance
“…However, estimates of compliance have typically been wide-ranging and untrustworthy. Compliance was 31-61% in a California reservoir (Rawstron 1971), 18-52% in an Oregon stream (Moring 1980), 15-36% in Texas bays (Green et al 1983), 67-92% in Missouri reservoirs (Colvin 1991), and 29-71% in Georgia reservoirs (Larson et al 1991). Tag reward schemes are typically used to encourage tag reporting.…”
Section: Discussionmentioning
confidence: 99%
“…However, estimates of compliance have typically been wide-ranging and untrustworthy. Compliance was 31-61% in a California reservoir (Rawstron 1971), 18-52% in an Oregon stream (Moring 1980), 15-36% in Texas bays (Green et al 1983), 67-92% in Missouri reservoirs (Colvin 1991), and 29-71% in Georgia reservoirs (Larson et al 1991). Tag reward schemes are typically used to encourage tag reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Synchrony of Largemouth Bass recruitment in four southeastern United States reservoirs was linked to reservoir discharge (Maceina and Bettoli 1998). Synchrony of crappie recruitment was reported for Tennessee reservoirs (Sammons et al 2002) but not for Missouri reservoirs (Colvin 1991). Across species, Ploskey et al (1996) observed synchronous increases of Largemouth Bass and Spotted Bass in Bull Shoals Lake during highwater periods.…”
mentioning
confidence: 97%
“…Recruitment can be erratic in reservoir populations of black bass and crappie Miranda 1998, 2001;Parkos and Wahl 2010), and these fluctuations ultimately affect angler success (Colvin 1991;McDonough and Buchanan 1991;Wrenn et al 1996). Due to this high interannual variability, important temporal trends in sport fish recruitment may be difficult to detect when using data collected over a short time period.…”
mentioning
confidence: 99%
“…Studies have documented various sampling methods to better understand and predict crappie year-class strength for management purposes (Tuberville 1979, Lewis and Siler 1980, Sammons and Bettoli 1998, St. John and Black 2004. Fall trap netting for age-1 and older crappie is a common sampling method used to determine year-class strength and predict harvest (Colvin 1991). However, initial assessment of a crappie year-class in their second year allows minimal time to analyze data, predict harvest, and prepare management plans for a water body.…”
Section: Introductionmentioning
confidence: 99%